Implementasi Sistem Informasi Pengelolaan Surat Akademik Mahasiswa Menggunakan Framework Laravel - Andreansyah, Tedy; Aryani, Diah; Sunarya, Po Abas (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
Mail management or archiving is very commonly carried out by an organization. At Esa Unggul University, the management of student academic letter needs is still done manually by the faculty administration staff, which is considered inefficient because there is only 1 faculty staff for each department, and they play a role in almost all faculty activities, so the management and service of academic letters has a slow process. Based on the problems found above, an academic letter management information system is proposed. This research is intended to be able to process student academic letter needs quickly and easily, so that it benefits both the students and the Faculty. The development method chosen for this system is prototyping using the Laravel framework, and producing an information system that can manage incoming and outgoing mail from the Esa Unggul University Faculty of Computer Science by the system. The benefits of this research include easing the work of the Faculty Admin, speeding up the process of serving academic letters, and reducing the risk of Human Error when managing academic letters